1994
DOI: 10.1007/bf00019045
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic characterization of reaction centers of the (M)Y210W mutant of the photosynthetic bacterium Rhodobacter sphaeroides

Abstract: The tyrosine-(M)210 of the reaction center of Rhodobacter sphaeroides 2.4.1 has been changed to a tryptophan using site-directed mutagenesis. The reaction center of this mutant has been characterized by low-temperature absorption and fluorescence spectroscopy, time-resolved sub-picosecond spectroscopy, and magnetic resonance spectroscopy. The charge separation process showed bi-exponential kinetics at room temperature, with a main time constant of 36 ps and an additional fast time constant of 5.1 ps. Temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 40 publications
7
70
0
Order By: Relevance
“…However, it may also slow down the recombination rate, thus allowing the primary donor to be reduced more efficiently while is still trapped, with the possibility for a new charge separation proceeding along the normally inactive chain and formation of @g (190). It was concluded from EPR and ODMR analysis that the structure of the primary donor did not change in the mutant (193). This was also confirmed by FTIR spectroscopy performed on the primary donor cation, which showed no detectable shift in charge density within the dimer (194).…”
Section: Chlorin and Bchl Radicalsmentioning
confidence: 68%
See 2 more Smart Citations
“…However, it may also slow down the recombination rate, thus allowing the primary donor to be reduced more efficiently while is still trapped, with the possibility for a new charge separation proceeding along the normally inactive chain and formation of @g (190). It was concluded from EPR and ODMR analysis that the structure of the primary donor did not change in the mutant (193). This was also confirmed by FTIR spectroscopy performed on the primary donor cation, which showed no detectable shift in charge density within the dimer (194).…”
Section: Chlorin and Bchl Radicalsmentioning
confidence: 68%
“…There it was found that replacement of the M210 tyrosine residue on the active side by phenylalanine leads to an increased efficiency of formation (BPh anion on the inactive B-side). This mutation is known to slow down the forward ET rate (191)(192)(193). However, it may also slow down the recombination rate, thus allowing the primary donor to be reduced more efficiently while is still trapped, with the possibility for a new charge separation proceeding along the normally inactive chain and formation of @g (190).…”
Section: Chlorin and Bchl Radicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…For preparation of reaction centers, the culture was centrifuged for 10 minutes at 5500  g and the pellet was re-suspended in 40 mL 0.1 M phosphate buffer (pH = 7.5). The RCs were isolated as described by Shochat et al (1994) 26 . A protein/pigment ratio A 280 /A 802 = 1.2 was measured in the absorption spectrum to assess the purity of the samples.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The clearest example was observed in the (M)Y210W mutant of Rb. sphaeroides where the tyrosine M210 had been replaced by tryptophan (Shochat et al 1994; van Noort 1994) with a major time constant of 33 and a minor one of 5 ps, but biphasic kinetics were also observed in other tyrosine mutants (Finkele et al 1990;Nagarajan et al 1990;Chan et al 1991;Hamm et al 1993;Jia et al 1993), in wild type Rb. sphaeroides (Mi]ller et al 1992;Duet al 1992;Hamm et al 1993) and in reaction centers of the green filamentous bacterium Chloroflexus aurantiacus (Becker et al 1991).…”
Section: Electron Transfermentioning
confidence: 99%